2021
DOI: 10.1073/pnas.2018043118
|View full text |Cite
|
Sign up to set email alerts
|

Cellular autofluorescence is magnetic field sensitive

Abstract: We demonstrate, by direct, single-cell imaging kinetic measurements, that endogenous autofluorescence in HeLa cells is sensitive to the application of external magnetic fields of 25 mT and less. We provide spectroscopic and mechanistic evidence that our findings can be explained in terms of magnetic field effects on photoinduced electron transfer reactions to flavins, through the radical pair mechanism. The observed magnetic field dependence is consistent with a triplet-born radical pair and a B1/2 value of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 39 publications
1
120
1
Order By: Relevance
“…However, a recent study reports that FAD RPs are MF-sensitive at physiological pH, albeit to a lesser extent than at acidic pH [55]. Moreover, a new study has revealed that flavin autofluorescence in HeLa cells is sensitive to MF [56]. Although this is not a functional response, their observations are consistent with an underlying RPM and represent an exciting example of an MF effect on a chemical reaction in living cells.…”
Section: Discussionmentioning
confidence: 91%
“…However, a recent study reports that FAD RPs are MF-sensitive at physiological pH, albeit to a lesser extent than at acidic pH [55]. Moreover, a new study has revealed that flavin autofluorescence in HeLa cells is sensitive to MF [56]. Although this is not a functional response, their observations are consistent with an underlying RPM and represent an exciting example of an MF effect on a chemical reaction in living cells.…”
Section: Discussionmentioning
confidence: 91%
“…Flavins generally provide a rich source of MFEs due to their ability to form RPs in photo-induced electron transfer reactions with various electron donors [252], both from the S and the T excited states [253]. Recently, the endogenous autofluorescence of HeLa cells has been found to respond to external MFs due to mitochondrial, triplet-born, flavin-containing RPs [254].…”
Section: Is Spin-correlation Common In Biology?mentioning
confidence: 99%
“…The fact that Luc-CTW(536)F is sufficient to support magnetosensitivity implies that a different, non-CRY, RP is involved. In this regard, it is notable that free FAD is capable of generating a magnetically sensitive RP via intramolecular electron transfer 7,34 . To explore this, we supplemented additional FAD to aCC via the internal patch saline.…”
Section: Free Fad Supports Magnetoreceptionmentioning
confidence: 99%